STRATEGI PEMERINTAHAN DESA DALAM MENINGKATKAN PENDAPATAN ASLI DESA (PAD) MELALUI SARANA OBJEK WISATA AIR TERJUN TH. 2020 (Studi kasus Desa Baru Kibul Kecamatan Tabir Barat Kabupaten Merangin Provinsi Jambi) - Mirza Febi Andriani; Dwiyani Sudaryanti; Siti Aminah Anwar (Universitas Islam Malang, 2021)
This study discusses the strategy of village government in increasing the Village's Original Income (PAD) through the Means of New Village Waterfall Tourism Object Kibul West Tabir District Merangin Jambi Province. This type of research is conducted descriptively Qualitatively. The results obtained from this study show that the village government's strategy in improving Village Native Income (PAD) through the means of waterfall attractions that is by maintaining the environment by keeping the waterfall clean so that the waterfall is maintained beauty and environment, Improving facilities in the tourist attraction area can cooperate with the government such as making rest facilities for visitors and businesses for the community, Urging the community to help cooperation in terms of preserving the environment such as greening and prohibiting the felling of trees, Making stalls selling food and drinks and opening souvenir shops in the tourist attraction area, Doing promotions by the management can be from social media such as instagram, facebook, and websites as well as from word of mouth promotion, Widening the road and giving fences on the edge of the ravine to make it safer for visitors.Keywords: Government Strategy, Village Native Income (PAD), Tourism Object Development